Study on the application of ionic liquids in bio-based lubricant for a sustainable machining process - Amiril, S. A.S. (2018)
Many factors tend to influence the increased demand in recent years, including stateof-the-art of effective and environmentally friendly metalworking fluids (MWFs). Bio-based lubricants from vegetable oils are highly biodegradable, non-toxic, pose good lubricating properties and low production costs. They have been widely perceived as a potential to reduce or replace the high dependency on the applications of petroleum-based MWFs. However, the inconsistent chemical composition and low thermal and oxidative stabilities of the natural oils leaves significant uncertainties about the overall sustainability performance of the bio-based MWFs. In this study, with the objective of achieving machining sustainability, a novel chemically modified Jatropha-based trimethylolpropane ester (MJO) was refined by mixing it with ionic liquids (ILs) additives. Two biocompatible and oil-miscible ILs; [P6,6,6,14][(iC8)2PO2] (PIL) and [N1,8,8,8][NTf2] (AIL) were mixed in the MJO at 1, 5, and 10 % weight concentrations. The newly refined mixtures are validated for their physicochemical and tribological properties as well as when being applied for minimum quantity lubrication (MQL) machining (orthogonal and oblique) of AISI 1045 steel. Results showed that, the lubrication performance of MJO+AIL10% and MJO+PIL1% outperformed the other lubricant samples used herein. With improved physicochemical and tribological performances, e.g. corrosion inhibition, friction and wear reduction, smooth surface finish and high machining efficiency, they recorded improvement in machining forces up to 12 %, cutting temperature up to 10 %, surface roughness by 7% and increased cutting tool life up to 50 % compared to the commercial synthetic ester-based MWF. A machining sustainability index evaluation was applied to the MQL machining scenario and based on results, MJO+PIL1% obtained the highest score for minimum lubricant’s cost, minimal energy consumption, or the best sustainability performance (4.08/5) and seconded by MJO+AIL10% (4.06). These novel bio-based MWFs provide another alternative to the world dominating mineral oil-based lubricants for “greener” and more sustainable working environment.